NALAR POLITIK KENEGARAAN DALAM ISLAM (Studi atas Pemikiran Muhammad Abiri>) - Yusdani, Yusdani (Universitas Islam Negeri Raden Intan Lampung, 2011)
Discourse of Islam vis-a-vis state is not apart from complexity of Arabic and Islamic reason. Muhammad ‘A<bid al-Ja>biri showed that complexity from sources of thought of contemporary socio-political science and sources of Arab-Islamic tradition itself. According to him, democratic leader type of Prophet is only applicative for Mecca and Medina society. Both communities are recognized applying nomadic tribe system, and recruitment of their leader was based on an adagium primus inter pares, just for the best and highly capable man can be elected by community. The past tradition cannot be applied wholly to present day without considering its socio-cultural aspect.